2012
DOI: 10.5194/hess-16-1203-2012
|View full text |Cite
|
Sign up to set email alerts
|

Implications of deep drainage through saline clay for groundwater recharge and sustainable cropping in a semi-arid catchment, Australia

Abstract: Abstract. The magnitude and timing of deep drainage and salt leaching through clay soils is a critical issue for dryland agriculture in semi-arid regions (<500 mm yr −1 rainfall, potential evapotranspiration >2000 mm yr −1 ) such as parts of Australia's Murray-Darling Basin (MDB). In this rare study, hydrogeological measurements and estimations of the historic water balance of crops grown on overlying Grey Vertosols were combined to estimate the contribution of deep drainage below crop roots to recharge and sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…4). Similar to the Murray-Darling Basin (Timms et al, 2012), the upper groundwater under vertisols in this aquifer were more saline than the deep groundwater (e.g., Fig. 1 in Baram et al, 2014).…”
Section: Impact Of Cultivation On Flushing Of the Unsaturated Zone Anmentioning
confidence: 93%
See 2 more Smart Citations
“…4). Similar to the Murray-Darling Basin (Timms et al, 2012), the upper groundwater under vertisols in this aquifer were more saline than the deep groundwater (e.g., Fig. 1 in Baram et al, 2014).…”
Section: Impact Of Cultivation On Flushing Of the Unsaturated Zone Anmentioning
confidence: 93%
“…A large bulk of literature from eastern Australia has reported increased deep-drainage and leaching of salts, and in some cases, salinization of aquifers under cultivated vertisols. A typical increase in deep drainage from < 1 mm yr −1 under native conditions to 10-20 mm yr −1 under rain-fed cropping were reported by Silburn et al (2009);Timms et al (2012) and Young et al (2014); whereas variable deep fluxes often in the 100's mm yr −1 range were reported for irrigated fields (mostly furrow-irrigated cotton; Gunwardena et al, 2011;Silburn et al, 2013;Weaver et al, 2013). These deep fluxes desolate salts that accumulated in the vadose zone in the native-vegetation period, moving them down towards the water table (Fig.…”
Section: Impact Of Cultivation On Flushing Of the Unsaturated Zone Anmentioning
confidence: 96%
See 1 more Smart Citation
“…The key control on regional water table dynamics is the exchange flux (EF), which is defined as the water flux into or out of the lower boundary of the soil control volume representing the vadose zone (Tang et al, 2007a;Timms et al, 2012). Since EF is substantially influenced by irrigation and the conversion from flood irrigation to drip irrigation, any study of groundwater table dynamics in this region requires that EF be appropriately quantified under these different circumstances.…”
Section: Z Zhang Et Al: Water-saving Irrigation and Implications Fomentioning
confidence: 99%
“…The occurrence of saline and brackish groundwater in reclaimed coastal aquifers worldwide is often a serious treat for agriculture (Da Lio et al, 2015;De Louw et al, 2011;Shi and Jiao, 2014;Timms et al, 2012). For this reason, the integrated management of water resources in coastal regions must be accomplished taking into account the exchanges between surface and groundwater bodies (Henriksen et al, 2008;Jønch-Clausen and Fugl, 2001).…”
Section: Introductionmentioning
confidence: 99%